2021
DOI: 10.3389/fpsyg.2021.782975
|View full text |Cite
|
Sign up to set email alerts
|

The Variability of Mental Timeline in Vertical Dimension

Abstract: People often use concrete spatial terms to represent abstract time. Previous studies have shown that mental timeline (MTL) is represented along a horizontal axis. Studies of the mental timeline have demonstrated that compared with English speakers, Mandarin speakers are more likely to think about time vertically (up-down) than horizontally (left-right/front-back). Prior studies have suggested that MTL in the up and down dimensions originated from temporal-spatial metaphors in language. However, there are still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Previous studies in the field of the Space-Time Association of Response Codes (STARC) have identified mental timelines associated with the “left–right” and “up-down” orientations ( Casasanto & Bottini, 2014 ; He et al, 2021 ). However, these investigations primarily explored the space–time mapping relationship from a one-dimensional spatial perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in the field of the Space-Time Association of Response Codes (STARC) have identified mental timelines associated with the “left–right” and “up-down” orientations ( Casasanto & Bottini, 2014 ; He et al, 2021 ). However, these investigations primarily explored the space–time mapping relationship from a one-dimensional spatial perspective.…”
Section: Discussionmentioning
confidence: 99%
“…This low-level embodied simulation establishes a mental timeline oriented from left to right. In contrast, the mental timeline associated with up-and-down orientation is primarily linked to high levels of verbal metaphors ( He et al, 2021 ). For instance, Chinese linguistic metaphors such as “morning ( )” and “afternoon ( )” equate to earlier and later times, respectively.…”
Section: Introductionmentioning
confidence: 99%